Towards a problem-value-constraint framework for maximising business value through minimising under design and over design. (2016) - Duan, Yucong; Fu, Guohua; Zhou, Nianjun; Sun, Xiaobing; Tang, Mingdong; Gao, Honghao
We have identified there is a need to systemically reduce the complexity and increase the robustness of developed service systems through a guided development process. We empirically choose under design (UD) and over design (OD) as core value assets to uniformly represent the target of managing the human errors and deficiencies during a development process. Based on the ideology of value driven design, we proposed the problem-value-constraint (PVC) approach as the framework of minimising UD and OD covering both IT concerns including functionalities and qualities and business concerns including value, cost, price and usage. Our PVC solution connects the characteristics including knowledge management, information transformation and business value. Our study showed that PVC is able to outline both business and technical characteristics and at the same time keep the simplicity of model structures.